Relationship between glenohumeral and thoracolumbar rotation range of motion in baseball players - Williams, J. G.; Darnall, L.; Schumann, C. (International Journal of Athletic Therapy & Training, 2020)
Baseball players have demonstrated greater thoracolumbar rotation (TLR) range of motion (ROM) toward their nonthrowing arm sides. This imbalance is thought to be compensatory to ROM deficiencies at the throwing arm`s shoulder. The purpose of this study was to examine the relationship between TLR and glenohumeral (GH) ROM measures (internal rotation, external rotation, horizontal adduction) among collegiate baseball players. Findings demonstrated limited and no relationships between TLR and GH ROM. Future research should advance these findings by examining symptomatic participants and hip ROM as additional variables. Doing so may enhance clinicians` abilities to comprehensively predict, prevent, detect, and treat movement deficiencies, and subsequent injuries, suffered by competitive baseball players.